PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID PADA MATERI SANGGUL UKEL TEKUK DAN SANGGUL UKEL KONDE (Beauty and Beauty Health Education, 2021)
This study aimed to know how to develop an android-based learning media, examine the learning media's validity, and determine students’ views toward using the learning media. The learning media was focused on the learning materials of Ukel Tekuk and Ukel Konde Indonesian traditional hair bun (sanggul) for beauty class students in SMK Negeri 3 Magelang. This learning media used PPE (Planning, Production, and Evaluation) as the development model. This research and development study result showed that the online software MIT app Inventor was used to develop the android-based learning media. This learning media was also valid since the total validity percentage of the multimedia experts, and the experts of learning materials was 86.6% with very distinct criteria. By using a questionnaire of media validation to find out the students’ views, it showed that the percentage of this learning media was 92% according to students’ perspectives. This value is classified as high criteria, so it cam be conclude that the perspectives of students on learning media for Belajar Sanggul are this learning media is easy to use and material presented is easy to understand.